Information transmission and core convergence in quasilinear economies - Yusuke Kamishiro; Roberto Serrano (Brown University, Department of Economics, 2008)
We study core convergence in interim quasilinear economies with asymmetric information, concentrating on core notions in which information is transmitted endogenously within coalitions and the incentive constraints are relevant. Specifically, we shall focus on the credible core and randomized mediated core concepts. We consider independent replicas of the basic economy: independent copies of the economy in which each individual's utility only depends on the information of the individuals who belong to the same copy. We provide an example in which core convergence does not obtain for the Dutta-Vohra credible core and for Myerson's randomized mediated core. On the other hand, we establish a positive convergence result for a refinement of Myerson's core for which information disseminates across coalitions within a given random blocking mechanism. Under some conditions, this core converges to the set of incentive compatible ex-post Walrasian allocations.
Keywords: C71; C72; D51; D82; 330; Core Convergence; Information Transmission; Coalitional Voting Mechanisms; Mediation; Rational Expectations Equilibrium